Hepatitis B in Medical Practice - Seroconversion status of medical students through enzyme immunoassays and its influential factors. (Research, Society and Development, 2022)
To determine, in medical students, knowledge; attitudes towards the social representation of hepatitis B; and immunological profile through enzyme immunoassays. This is an epidemiological, exploratory study conducted with medical students from a private higher education institution. For data collection, a self-administered instrument was applied; verification of the immunization card; and proof of the students' serological status. Data were analyzed using the Statistical Package for the Social Science software, using bivariate analysis and logistic regression. A total of 84 students participated in the study, most of them from the second academic year of the medical course (59.5%). Some gaps in students' knowledge about the transmissibility of the disease were noticed, showing a statistically significant association between immunization status and etiologic agent (p